Liver Transplantation Beyond Milan Criteria - Lingiah, Vivek A (J Clin Transl Hepatol, 2020)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide, being the fifth most common cancer and the third most common cause of cancer-related mortality. The incidence of HCC has been rising in the USA over the last 20 years. Liver transplantation is an optimal treatment option, as it eliminates HCC as well as the underlying liver disease. The Milan criteria (1 lesion greater than or equal to 2 cm and less than or equal to 5 cm, or up to 3 lesions, each greater than or equal to 1 cm and less than or equal to 3 cm) have been adopted by many transplant societies worldwide as the criteria to determine whether patients with HCC can move forward with liver transplantation. However, many believe that the Milan criteria may be too strict in regard to its size requirements for lesions. This has led to a number of expanded criteria for liver transplantation, concerning both overall size and number of lesions, as well as incorporation of other markers of tumor biology. Tumor markers, such as alpha-fetoprotein, can also be used to follow treatment of HCC and possibly exclude patients from transplant. HCC presenting beyond Milan criteria can also be down-staged with locoregional therapy. Monitoring response to locoregional therapy and longer wait times after locoregional therapy prior to transplant can serve as surrogate markers of tumor biology as well.